Contextualizing chemistry teaching: awareness and traffic safety from an educational approach using the breathalyzer test - Viana, Jonathan Pereira; Silva, Felipe dos Santos; Mendes, Ana Nery Furlan (Brazilian Journal of Production Engineering, 2023)
In order to promote improvements in chemistry teaching, the contextualization of content plays a fundamental role in the teaching-learning process. Thus, the importance of contextualizing the content worked on in the classroom goes beyond simple theoretical examples and applications of knowledge, as it is necessary to incorporate local reality and culture into the school context. In this sense, the approach to monitoring alcohol consumption by drivers, using the so-called "breathalyzer test", stands out as an example of integrating Science, Technology, Society and Environment (STSA) into chemistry teaching. In this work, we proposed the creation of didactic material that was presented to the students of a state public school in São Mateus/ES in the form of a workshop, which simulates how a breathalyzer works. The workshop was developed in two parts, the first of which was a round table discussion about how breathalyzers work and the harmful effects of alcohol consumption, and the second part was a breathalyzer test experiment. The workshop made it possible to work on chemical concepts, discuss social issues and build up knowledge together with the students about the health and social implications of excessive alcohol consumption.